2005
DOI: 10.1159/000083033
|View full text |Cite
|
Sign up to set email alerts
|

Success of a Smoking Cessation Program among Smoking Relatives of Patients with Serious Smoking-Related Pulmonary Disorders

Abstract: The aim of the study was to investigate the success of a smoking cessation program among the smoking relatives of patients with serious smoking-related disorders and to determine whether having a relative with such a disorder influences the rate of success of the program. The relatives of patients with chronic obstructive pulmonary disease (COPD) and lung cancer who wanted to quit smoking were included in the smoking cessation program (group I, n = 34). During the same period, the same number of subjects with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
(10 reference statements)
1
11
0
Order By: Relevance
“…Research into the role of having a family member with a lifetime history of cancer on quitting intention has been sparse. One study showed that family members of cancer patients may be more aware of the negative health effects of smoking [31], but that this may not necessarily translate into increased readiness to quit or likelihood of maintaining abstinence [19,32]. A recent cross-sectional study conducted in Australia showed that approximately one-third (36%) of individuals with a friend or relative with cancer reported quitting smoking [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research into the role of having a family member with a lifetime history of cancer on quitting intention has been sparse. One study showed that family members of cancer patients may be more aware of the negative health effects of smoking [31], but that this may not necessarily translate into increased readiness to quit or likelihood of maintaining abstinence [19,32]. A recent cross-sectional study conducted in Australia showed that approximately one-third (36%) of individuals with a friend or relative with cancer reported quitting smoking [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of this circumstance is not clear. Two studies were found that compared smoking cessation rates among smokers with a family member who had a smoking-related disorder versus smokers without a family member with a smoking-related condition failed to show a between-group difference in quit rates [18,19]. The limited amount of research in this area renders the effect of having a family member who smokes with cancer on a smokers' quitting intention and behavior an open question.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21] In studies from Turkey, the level ranges between 10 and 55.2%. [22][23][24][25][26][27][28][29] One study showed that intensive clinical interventions maintained over 5 years reduced mortality by 5%. 30 International long-term studies report cessation levels between 28% and 37%.…”
Section: Resultsmentioning
confidence: 99%
“…1,3,7 However, despite intensive treatment programs, long-term abstinence (6 months or more) was under 50%. [15][16][17][18][19][20][21] Two studies reported high cessation rates (53.5% and 43.2%) at the end of the first year. 22,23 In both of those studies, the authors suggested that, multidisciplinary smoking cessation clinics with regular …”
Section: Discussionmentioning
confidence: 99%